Penerapan Model Pembelajaran PAIKEM dalam Meningkatkan Aktivitas Belajar Siswa - Imelvia Munu; Nur Azizah Rasid (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Effective learning involves active student involvement. The PAIKEM (Active, Innovative, Creative, Effective, and Enjoyable Learning) model emphasizes activeness, creativity, and a fun learning atmosphere. In this model, students are invited to be directly involved in the learning process, either through discussions, questions and answers, or group work that facilitate the development of their social and cognitive skills. This article aims to examine the application of the PAIKEM learning model in improving student learning activities through a literature review of ten scientific journals indexed by Google Scholar. The results show that PAIKEM increases participation in discussions, courage to ask questions, group collaboration, and learning motivation. In addition, this model also facilitates the development of students' critical and creative thinking skills, creating a fun and challenging learning atmosphere. The implementation of PAIKEM in learning has a positive impact on improving overall student learning outcomes. Thus, the PAIKEM learning model can be an effective alternative for teachers to create more active, meaningful learning, and oriented towards the development of student competencies as a whole.